2013
DOI: 10.1037/a0031388
|View full text |Cite
|
Sign up to set email alerts
|

Universal and culture-specific factors in the recognition and performance of musical affect expressions.

Abstract: We present a cross-cultural study on the performance and perception of affective expression in music. Professional bowed-string musicians from different musical traditions (Swedish folk music, Hindustani classical music, Japanese traditional music, and Western classical music) were instructed to perform short pieces of music to convey 11 emotions and related states to listeners. All musical stimuli were judged by Swedish, Indian, and Japanese participants in a balanced design, and a variety of acoustic and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
156
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(174 citation statements)
references
References 76 publications
8
156
1
9
Order By: Relevance
“…The parallelism of human emotion expression in speech and music has been demonstrated by a comprehensive review of empirical studies on patterns of acoustic parameters in these two forms of human affect communication (Juslin and Laukka, 2003). The assumption of powerful "affect primitives" in speech and language is also supported by research on the recognition of emotion in speech (Bryant and Barrett, 2008;Laukka et al, 2013b;Pell et al, 2009;Sauter et al, 2010;Scherer et al, 2001) and music (Laukka et al, 2013a). This research has generally shown the existence of both a fairly high degree of universality of the underlying expression and recognition mechanisms and of sizeable differences between cultures, especially for self-reflective, social, and moral emotions.…”
Section: Introductionmentioning
confidence: 97%
“…The parallelism of human emotion expression in speech and music has been demonstrated by a comprehensive review of empirical studies on patterns of acoustic parameters in these two forms of human affect communication (Juslin and Laukka, 2003). The assumption of powerful "affect primitives" in speech and language is also supported by research on the recognition of emotion in speech (Bryant and Barrett, 2008;Laukka et al, 2013b;Pell et al, 2009;Sauter et al, 2010;Scherer et al, 2001) and music (Laukka et al, 2013a). This research has generally shown the existence of both a fairly high degree of universality of the underlying expression and recognition mechanisms and of sizeable differences between cultures, especially for self-reflective, social, and moral emotions.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, sadness expressed by music is associated with a consistent set of affective cues [18], which may convey the emotion even across cultures [19] and to young children [20].…”
mentioning
confidence: 99%
“…Hal ini menjelaskan sisi lain dari adanya pengaruh budaya dalam musik. Penelitian serupa dilakukan oleh Laukka et al (2013), yang mencoba menggali apakah emosi bisa dikomunikasikan dengan musik dalam setting kultur yang berbeda. Penelitian tersebut dibuat karena dilatarbelakangi perdebatan apakah ekspresi dari musik merupakan hal yang dapat diidentifikasi secara universal atau kultural.…”
Section: Musik Sebagai Sarana Terapi: Bebas Budaya Vs Terikat Budayaunclassified
“…Musik sebagai fenomena muncul di berbagai kultur, ditambah bahwa unsur utama dari musik seperti pitch dan durasi merupakan aspek yang dapat dikenali secara universal. Di sisi lain, musik juga dianggap sebagai produk kultur karena persepsi dan kognisi dari struktur elemen musik yang dikenali secara berbeda oleh manusia dengan background kultur yang berbeda (Laukka, Eerola, Thingujam, Yamasaki, & Beller, 2013).…”
Section: Musik Sebagai Sarana Terapi: Bebas Budaya Vs Terikat Budayaunclassified
See 1 more Smart Citation